INTERACTIVE TEACHING METHOD IN RUSSIAN LANGUAGE LESSONS AS A WAY TO INCREASE STUDENTS' COGNITIVE ACTIVITY - Ramazanova Roza Abilovna (Journal of Higher Education and Academic Advancement, 2024)
This article actualizes the need to introduce an interactive teaching method into the educational process. The author gives examples of the most common techniques by which positive results can be achieved in the learning process.